Development of LKPD Based on Think Talk Write on the Material of Basic Laws of Chemistry Class X - Gani*, Abdul; Yunistika, Ninda; Nasir, Muhammad; Zulfadli, Zulfadli; Winarni, Sri; Habibati, Habibati (JURNAL PENDIDIKAN SAINS (JPS), 2023)
The material on the basic laws of chemistry taught at the high school level so far is still not optimal according to the demands of the curriculum. This can be seen based on the low national exam results. The national exam scores for basic chemical laws in 2018 and 2019 were 16.6 and 35.2, respectively. This study aims to: (1) Describe the feasibility of TTW based LKPD developed on basic chemical laws material, (2) Describe students responses to TTW based LKPD developed on basic chemical laws material, (3) Describe educators responses to TTW based LKPD developed on basic chemical laws material. This research method uses R&D with the 4-D model, namely define, design, develop, and disseminate. The subjects of this study were students of class X IPA 1 SMA Negeri 12 Banda Aceh totaling 25 people. Data collection was carried out using instruments. The research instrument is the LKPD validity assessment sheet by experts, a questionnaire sheet for students and educators responses. The results of the feasibility assessment of LKPD obtained very good, namely 93.3%. The responses of students and educators to the LKPD each obtained 86% and 94.8% in the very good category. Based on the results of the study, it can be concluded that the LKPD based on think talk write on the material of the basic laws of chemistry is feasible to use as teaching material